Biogeography of different life forms of the southernmost neotropical tank bromeliad. (9th June 2021) - Barberis, Ignacio M.; Mogni, Virginia Y.; Oakley, Luis J.; Vogt, Christian; Prado, Darién E.
Abstract: Aim: Factors affecting bromeliad distribution depend on the life forms of the studied species; some could grow as terrestrial, saxicolous, or epiphytic depending on the type of habitat. We analysed the distribution patterns of the life forms of a bromeliad species in different biogeographic domains and associated them with environmental variables and vegetation types. Location: Chaquenian, Amazonian, and Seasonally Dry Tropical Forest domains; South America. Taxon: The tank bromeliad Aechmea distichantha (Bromeliaceae: Bromelioideae). Methods: We compiled records of the biogeographic distribution and the vegetation types where A . distichantha occurs based on bibliographic data, digital datasets, herbaria, and personal observations. We associated the distributional records of this species with altitude, five selected bioclimatic variables, four soil variables, and with the vegetation types where it occurs. Results: A . distichantha has been recorded as epiphytic, terrestrial and saxicolous in all biogeographic domains but showed contrasting patterns in life form proportions among them. In the Amazonian domain, characterized by evergreen tropical and subtropical forests with high precipitation, it mainly grows as epiphytic. In the Chaquenian domain, dominated by xerophytic forests with low rainfall, high soil pH and base saturation, it mainly grows as terrestrial, whereas in the Seasonally Dry Tropical Forest domain, the three life forms were recorded in similar proportions. In azonal plant communities of all domains, it mainly grows as saxicolous. Main Conclusions: This tank bromeliad species can thrive in sites with contrasting habitat and environmental conditions. Its ability to survive in different environments could be associated with its high frost tolerance, the presence of the CAM photosynthetic pathway, a well‐developed phytotelma, and high phenotypic plasticity. The life form prevailing in each domain is influenced by water availability (i.e., the quantity of water available during each year, the precipitation in the driest month, and the plant water supply relative to demand).